Islam and Religious Pluralism in the Perspective of the Al-Qur'an and Tafsir Scholars - Achmad Haikal Azumardi Azra; Bilqis Cahya Ratri; Choirul Azam Firdaus (Educational Foundation for Qur'anic Exegesis and Hadith Studies (Yayasan Pendidikan Tafsir Hadis), 2023)
This research aims to examine the perspective of the Al-Qur'an and interpretive scholars regarding religious pluralism. This research uses a literature review method or literature research, data collection in this research uses qualitative methods. The results of this research show that religious pluralism is an understanding or view of religious pluralism. Pluralism is an understanding that respects the differences in a society and allows different groups to maintain their respective cultural diversity. The verses of the Qur'an that explain pluralism include Q.S. Al-Baqarah verse 62, and Q.S. Al-Baqarah verse 256. The Qur'an commands us to respect each other's differences, tolerate each other, help each other, and build ukhuwah within. We must also adhere to our respective religions and compete in goodness. We as Muslims may acknowledge the existence of religious plurality in this world, but only to the extent of acknowledging its existence, not its truth.